Organizational Communication as A Pillar of Resilience for Indonesian Cargo Airlines in the Post Covid 19 Crisis - Kusumawati, Irma; Suryana, Asep; Venus, Anter; Arifin, Hadi Suprapto (Journal of Posthumanism, 2025)
The COVID-19 pandemic has been a major test of resilience for the global aviation industry, particularly the air cargo sector, which plays a vital role in maintaining logistic supply chains. This study examines how organizational communication serves as a key pillar in building resilience among Indonesian cargo airlines following the crisis, with a focus on the case study of PT. Tri M.G. IntraAsia Airlines. Using a descriptive qualitative approach through in-depth interviews, observation, and internal document analysis, this study found that integrating formal and informal communication was key to the organization’s success in maintaining operations, supporting employees’ psychological stability, and accelerating service recovery. Formal communication provides structure and clarity in decision-making, while informal communication strengthens solidarity, trust, and the speed of information flow. When combined with communication digitization and empathetic leadership, both together form an adaptive long-term resilience infrastructure capable of withstanding repeated disruptions. Theoretically, this study extends the application of Situational Crisis Communication Theory (SCCT) by positioning organizational communication as the foundation of strategic resilience. Practically, the study offers recommendations for the cargo industry to develop communication strategies that are symmetrical, empathetic, and technology-based to strengthen organizational competitiveness and sustainability in the post-crisis era.